Sport Generated by New Media in the COVID-19 Crisis: An Analysis of Female Fitness Enthusiasts - Matteucci, Ivana (Italian Sociological Review, 2021)
The global spread of the COVID-19 pandemic has lead to the integration of physical activity, through the Web, into everyday life, giving rise to new concepts of identity and unprecedented forms of sociality. The aim of the present investigation was to understand and interpret the experiences of a group of Web users, namely their multi-faceted digital identity, social interactions, and the emerging relationship between their offline and online lives. We were thus able to verify the hypothesis that the online and offline worlds can become integrated generating an augmented reality both in terms of identity and relationships. Specifically, we investigated a Facebook group of female fitness enthusiasts, who were obliged to alter their approach to sport and physical activity following the adoption of government measures to contain the spread of the virus: lockdown (phase 1) and post-lockdown (phase 2). The research was conducted using both qualitative methodology, consisting of participant observation and semi-structured interviews, and the quantitative tool of the questionnaire. Our results show that the physical world and digital world brought together digital communication strategies and real physical bodies moving towards a connected integrated model of sports and physical activity.